2014
DOI: 10.1530/eje-14-0013
|View full text |Cite
|
Sign up to set email alerts
|

THERAPY OF ENDOCRINE DISEASE: The challenges in managing giant prolactinomas

Abstract: Giant prolactinomas are rare tumours, representing only 2-3% of all prolactin (PRL)-secreting tumours and raising special diagnostic and therapeutic challenges. Based on several considerations developed in this review, their definition should be restricted to pituitary adenomas with a diameter of 40 mm or more, significant extrasellar extension, very high PRL concentrations (usually above 1000 mg/l) and no concomitant GH or ACTH secretion. Giant prolactinomas are much more frequent in young to middle-aged men … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
166
2
13

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 158 publications
(191 citation statements)
references
References 125 publications
(229 reference statements)
5
166
2
13
Order By: Relevance
“…В настоящее время основным методом лечения пролактином, в том числе гигант-ских размеров, является терапия каберголи-ном [4,5]. Каберголин снижает/нормализует уровень ПРЛ в крови и уменьшает размеры опухоли, что приводит к регрессу зритель-ных и неврологических симптомов заболева-ния [6,7].…”
Section: Discussionunclassified
“…В настоящее время основным методом лечения пролактином, в том числе гигант-ских размеров, является терапия каберголи-ном [4,5]. Каберголин снижает/нормализует уровень ПРЛ в крови и уменьшает размеры опухоли, что приводит к регрессу зритель-ных и неврологических симптомов заболева-ния [6,7].…”
Section: Discussionunclassified
“…10, 11 Maiter D et al in 2014 reviewed the management of giant prolactinoma cases and found that the extensive tumours are usually not completely resectable and neurosurgery has significant morbidity and mortality. 12 So additional therapy after operation using conventional external radiation may be needed, but it takes several years to achieve endocrinological remission and risk for panhypopituitarism or visual disturbances exists.…”
Section: Discussionmentioning
confidence: 99%
“…Six (13%) and nine (50%) of the patients included in these two cohorts had pituitary surgery compared to 69% in the current series [5]. Maiter D & Delgrange E summarized the efficacy of primary treatment with dopamine agonists in 13 other cohorts of patients with giant prolactinomas including 140 subjects (86% males) [1]. PRL normalized in 60% of the patients treated with cabergoline, bromocriptine, or pergolide, and the tumors have shrunk (>30% decrease in tumor diameter, or >65% reduction in tumor volume) in 74% of the subjects.…”
mentioning
confidence: 82%
“…Among the affected patient population, females usually harbor microadenomas, whereas the larger macroadenomas are diagnosed in males and post-menopausal women. The very large and invasive prolactin (PRL)-secreting tumors measuring >40 mm in diameter with baseline PRL levels >1000 ng/ml but typically much higher, the giant prolactinomas, represent 3-5% of all PRL-adenomas, and appear with a male to female ratio of about 9:1 [1,2]. Usually, there is an association between tumor size and baseline serum PRL level, but this association is not always kept.…”
mentioning
confidence: 99%